KORELASI ANTARA HASIL BELAJAR DAN METAKOGNISI SISWA SEKOLAH DASAR DI NANGA PINOH, KALIMANTAN BARAT - Rindah Permatasari (Universitas Islam Lamongan, 2019)
The low student learning outcomes are caused by various aspects, one of them is student awareness of the importance of learning. The purpose of this study was to analyze the correlation between students' science learning outcomes and metacognitive skills in elementary school students in Nanga Pinoh. This research is a quantitative study using One Group Pretest-Posttest design. Data was taken from 67 students in 3 State Elementary Schools, namely SDN 28, SDN 06, and SDN 03 Nanga Pinoh. The instruments used were test questions and the Metacognitive Skills Questionnaire. Data were analyzed descriptively quantitatively. The results of data analysis using Pearson Product Moment Correlation shows that there is a significant positive relationship between student academic procrastination and student cognitive ability with the acquisition (rcount) = 0.993 at the significance level of 0.00. This means that the higher the level of metacognitive skills of students, the student learning outcomes will also increase. The coefficient of determination shows 0.98 or 98%, this means that student learning outcomes are determined by the level of metacognitive skills of students, while 2 % of student learning outcomes are determined by other factors such as health, the presence or absence of problems and others